Public Diplomacy in ASEAN Youth Interfaith Camp (AYIC) to Develop Indonesia’s Image in ASEAN - Rika Rahmayuni; Darmansjah Djumala (Soshum: Jurnal Sosial dan Humaniora, 2023)
This research focuses on Indonesia's influential position in ASEAN and its image, considering both strengths and weaknesses. Despite being known for natural beauty and cultural richness, the country faces challenges that affect how it is perceived globally. The study examines the ASEAN Youth Interfaith Camp (AYIC) as a public diplomacy tool aimed at enhancing Indonesia's image. Through qualitative research, using official documents and interviews, the study explores how AYIC contributes to projecting Indonesia as a tolerant and harmonious nation. The research sheds light on the program's success in dispelling religious stereotypes, ultimately improving Indonesia's international image and advancing its national interests through soft power.